2008
DOI: 10.1212/01.wnl.0000265401.62434.36
|View full text |Cite|
|
Sign up to set email alerts
|

Intranasal insulin improves cognition and modulates β-amyloid in early AD

Abstract: The results of this pilot study support further investigation of the benefits of intranasal insulin for patients with Alzheimer disease, and suggest that intranasal peptide administration may be a novel approach to the treatment of neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
552
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 737 publications
(571 citation statements)
references
References 31 publications
14
552
1
4
Order By: Relevance
“…Recent reports are consistent with the possibility that one such protective mechanism could be provided by CNS insulin signaling. Insulin plays a key role in plasticity mechanisms in the CNS (26,27) and it recently has been shown that insulin and the insulin-sensitizing drug rosiglitazone improve cognitive performance in mouse models of AD and in patients with early AD (28)(29)(30). Conversely, insulin-resistant type 2 diabetes patients show significantly increased risk for developing AD (31).…”
mentioning
confidence: 99%
“…Recent reports are consistent with the possibility that one such protective mechanism could be provided by CNS insulin signaling. Insulin plays a key role in plasticity mechanisms in the CNS (26,27) and it recently has been shown that insulin and the insulin-sensitizing drug rosiglitazone improve cognitive performance in mouse models of AD and in patients with early AD (28)(29)(30). Conversely, insulin-resistant type 2 diabetes patients show significantly increased risk for developing AD (31).…”
mentioning
confidence: 99%
“…Specifically, studies that have involved the intranasal infusion of insulin (i.e. direct delivery of insulin into the central nervous system) have suggested that insulin administration can enhance memory performance in the absence of changes in plasma glucose or insulin (Reger et al, 2006;Reger, Watson, Green, Wilkinson et al, 2008). Craft and colleagues (1994) observed a gender difference in glucose facilitation of memory, in that glucose was observed to facilitate episodic memory in males, but this effect was not observed in female participants.…”
Section: Insulinmentioning
confidence: 99%
“…Systemic or intranasal administration of insulin enhances learning and memory and has been proposed as a treatment for Alzheimer's disease [68]. These findings have led to the hypothesis that insulin insufficiency may lead to the defects in neurocognition commonly observed in MDD (discussed below).…”
Section: Endocrinological Factorsmentioning
confidence: 99%